2008
DOI: 10.1002/pits.20302
|View full text |Cite
|
Sign up to set email alerts
|

Engaging students at school and with learning: A relevant construct for all students

Abstract: There is consensus that student engagement is a relevant and multidimensional construct that integrates students' thoughts, feelings, and behaviors (Fredericks, Blumenfeld, & Paris, 2004;Furlong et al., 2003). Most typically, researchers have incorporated a three-part typology, emphasizing affective, behavioral, and cognitive dimensions of engagement (Finn, 1989;Fredericks et al., 2004;Jimerson, Campos, & Greif, 2003). Practitioners, however, have often been highly influenced by academic engaged time (i.e., ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
0
16

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(109 citation statements)
references
References 15 publications
1
92
0
16
Order By: Relevance
“…The results of the present study shed light in this respect. The findings provide support to Furlong and Christenson (2008) that student engagement "is highly influenced by contextual factors -home, school, and peers" (p. 366). Indeed, the key to enhance boys' engagement in school may lie in the enhancement of support from teachers, parents, and peers.…”
Section: Implications For the Work Of School Psychologistssupporting
confidence: 64%
“…The results of the present study shed light in this respect. The findings provide support to Furlong and Christenson (2008) that student engagement "is highly influenced by contextual factors -home, school, and peers" (p. 366). Indeed, the key to enhance boys' engagement in school may lie in the enhancement of support from teachers, parents, and peers.…”
Section: Implications For the Work Of School Psychologistssupporting
confidence: 64%
“…While the current study did not examine student achievement, the results of this study suggest that flipped classrooms may impact student engagement -which many link to achievement (e.g., Carini, Kuh, & Klein, 2006;Furlong & Christenson, 2008;Lazowski & Hulleman, 2016). As suggested by numerous research articles and confirmed by our research, however, factors affecting student engagement in both flipped and non-flipped classes are numerous and varied (Fredricks, Blumenfeld, & Paris, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…There is growing evidence that student engagement, a multi-dimensional construct that Astin (1984, p. 297) defines as "total amount of physical and psychological energy that the student devotes to the academic experience," is directly related to student achievement (Carini, Kuh, & Klein, 2006;Furlong & Christenson, 2008;Lazowski & Hulleman, 2016;Lee & Smith, 1993;Willingham, Pollack, & Lewis, 2002). It is for that reason that student engagement is, itself, becoming an objective of classroom instruction.…”
Section: Introductionmentioning
confidence: 99%
“…We would argue that clinicians are not well-positioned to judge this subjective, internal state and that their 'assessment' of a patient's engagement may at best provide only a partial view of engagement and at worst, reflect an inaccurate picture [45]. It could be anticipated that the patient may have a different perspective that should be considered [32,40,57,66]. …”
mentioning
confidence: 99%